SEXUAL HAZING AND ABUSE PHENOMENA IN TONI MORRISON THE BLUEST EYE - Ken Kirana Swasti Ratu; Mateus Rudi Supsiadji (Anaphora : Journal of Language, Literary, and Cultural Studies, 2019)
This essay focuses the discussion on sexual hazing and sexual abuse phenomena which had happened to several roles in Toni Morrison’s The Bluest Eye. The method used was a descriptive confirmatory method meaning the method approached and analyzed the study based on the confirmation of the theory and data from its own novel. In addition, this essay applied some points about socialist feminism as the additional reference of discussion. Socialist feminism itself is a branch of feminism that focuses upon both the public and private spheres of women’s life and argues that liberation can only be achieved by working to end both the economic and cultural resources of women’s oppression. The result showed Cholly had an sexual experience with humiliation, Frieda who was experienced abuse from Mr. Henry as well as Pecola, the lead role of this novel who had sexual hazing through rape.